2014 FINRA analysis: a blockbuster year for fines. Issue 2 (6th July 2015) - Rubin, Brian; McCormick, Andrew M.
Abstract : Purpose: – To analyze the cases and sanctions FINRA reported in 2014 and prior years to evaluate what issues may be important for broker-dealers and their representatives in the future. Design/methodology/approach: – This article discusses the overall statistics for cases reported by FINRA in 2014 and then focuses on the top enforcement issues for FINRA and some of the key cases. All of this analysis includes a comparison to enforcement statistics from prior years to help identify potential trends. Findings: – This article concludes that 2014 was a blockbuster year for FINRA as the fines imposed by the regulator increased by 125 per cent. This article also finds that while FINRA is still focusing on many of the same issues as before, including advertising and trade reporting, other issues, such as anti-money laundering, received a significant spike in attention in 2014. Originality/value: – This article contains valuable information about recent FINRA enforcement activity and practical guidance from experienced securities lawyers.